Texture and water holding capacity of oat drinks fermented with lactic acid bacteria, bifidobacteria and Propionibacterium - Małgorzata Ziarno; Dorota Zaręba; Iwona Ścibisz; Mariola Kozłowska (International Journal of Food Properties, 2024)
Oats are among the most valued cereal commodities in the food market and are considered an exceptional grain. This study aimed focuses on assessing the impact of starter cultures, including lactic acid bacteria (i.e. Streptococcus thermophilus and Lactobacillus delbrueckii subsp. bulgaricus), Bifidobacterium animalis subsp. lactis Bb-12, and Propionibacterium freudenreichii subsp. shermanii PS-4, on selected quality parameters of yogurt-type fermented oat drinks. These drinks were produced by aqueous extraction of commercial oat flakes in drinking water. Acidification curves were determined during fermentation, and the oat drinks were subsequently stored at 6°C for 35 days. Throughout the study, acidity (measured by pH values), populations of lactic acid bacteria, bifidobacteria, and propionibacteria, as well as texture attributes (hardness and adhesiveness), water-holding capacity, and selected carbohydrate content were examined at the end of fermentation and every 7 days during storage. Results indicated that the addition of bifidobacteria and/or propionic acid bacteria in oat drink cultures expedited and improved the acidification process, resulting in a drink with a lower pH. Furthermore, the incorporation of propionic acid bacteria enhanced the water-holding capacity of the drink. Although the fermentation process had no significant impact on the texture of the oat drinks, the introduction of bifidobacteria reduced the adhesiveness of the final product. Carbohydrate content in the oat drinks diminished during fermentation, with sucrose experiencing the most substantial reduction. In conclusion, the study suggests that supplementing oat drink cultures with bifidobacteria and/or propionic acid bacteria proves to be an effective strategy for enhancing both the quality and shelf life of the final product.